Impact of the COVID-19 Pandemic and Public Restrictions on Outcomes After Catheter Ablation of Atrial Fibrillation - Kim, Daehoon; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Background: Here we aimed to analyze changes in the outcomes of atrial fibrillation (AF) catheter ablation (AFCA) during the coronavirus disease 2019 (COVID-19) pandemic and examine the relationship between rhythm outcomes and the stringency of government social distancing measures. Methods: We included 453 patients who underwent de novo AFCA between May 2018 and October 2019 (pre-COVID-19 era) and 601 between November 2019 and April 2021 (COVID-19 era). The primary outcome was late recurrence, defined as any episode of AF or atrial tachycardia documented after a 3-month blanking period. A multivariable Cox regression analysis was performed to estimate the relative hazards of AF recurrence in the two eras. Results: In the study population (24.3% women; median age, 60 years), 660 (62.6%) patients had paroxysmal AF. Among those with paroxysmal AF, the late recurrence rate was significantly lower in the COVID-19 era than in the pre-COVID-19 era (9.4% vs. 17.0%, respectively, log-rank P=0.004; adjusted hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.35–0.90) during a median follow-up of 11 months. In patients with persistent AF, the late recurrence rate did not significantly differ between the pre-COVID-19 and COVID-19 era groups (18.9% vs. 21.5%, respectively; log-rank P=0.523; adjusted HR 0.84, 95% CI 0.47–1.53) during the median follow-up of 11 months. Conclusion: A decrease in AF recurrence after catheter ablation was observed in patients with paroxysmal AF during the COVID-19 outbreak, whereas no change was observed in those with persistent AF.